Synthesis and characterization of molecularly imprinted polymer in oleic acid isolation from palm fatty acid distillate wastes - Abu Samah, Nurlin; Azhar, Siti Maizatul Ameera; Maniam, Gaanty Pragas (The Malaysian Analytical Sciences Society, 2023)
In this study, molecularly imprinted polymer-oleic acid (MIPOA) was synthesized using oleic acid (OA) as the template via bulk polymerization. The objective of this study was to characterize the MIPOA as an adsorbent for the isolation of OA from palm fatty acid distillate (PFAD) waste, using thermogravimetric analysis (TGA) and Brunauer-Emmett-Teller (BET) analysis. Isolation method of OA from PFAD waste using MIPOA via esterification reaction in methanol and detection of OA by using gas chromatography–mass spectrometry (GC-MS) showed that MIPOA was capable of isolating OA from PFAD waste sample at 99.99% of isolation efficiency. Findings obtained from TGA results showed that MIPOA was less thermally-stable compared to NIP at higher temperature as the percentage weight loss of MIPOA was higher than NIP. At 215 oC, the weight loss of MIPOA (9.36%) was higher compared to NIP (6.55%) as a control due to the less branch of cross-linked polymer was successfully synthesized. Higher surface area in MIPOA compared to NIP was successfully proven in this experiment. In addition, the presence of OA as a template leaves the cavities during MIPOA washing contributes to the increase of the surface contact. Due to its high surface area and ease of degradation by external energy from heating when compared to NIP (which act as control), MIPOA has a high porosity and an abundance of an organic cross-linkage network. From BET analysis, surface area of MIPOA was 390.52 m2/g and this value was relatively high in isolation efficiency for the isolation of OA methyl ester. MIPOA displays type I isotherms which indicates that the MIPOA was microporous. These results proved that MIPOA can be employed as a potential adsorbent to isolate OA from PFAD waste.